Kolaborasi Pengajar dengan Komunitas SARISEJAYA Dalam Meningkatkan Pembelajaran Sejarah Dan Karakter - Agus Susilo, Yohana Satinem, Ahmad Marsehan (LP4MK STKIP PGRI Lubuklinggau, 2024)
The role of History learning in space and time is very important. The values contained in the study of History are a provision for the next generation of the Indonesian nation in the future. The purpose of this research is the collaboration of teachers with the SARISEJAYA Community in improving History learning and character. In developing this research, researchers used descriptive qualitative methods. This descriptive research method combined with a qualitative approach produces a work that is authentic and in accordance with the needs. In supporting the analysis system, this research uses data sources through direct observation studies in the field of how the History learning process is at the secondary and higher education levels. Then supporting reference sources from scientific papers journals and books that help in this research. History learning and character values are how the role of History learning to continue to be raised to become a favorite learning. History learning itself has local wisdom values that can help increase understanding for students. For the introduction of History learning based on local wisdom, of course, it requires a big struggle such as opportunities in the combination between the education level and the SARISEJAYA Community. Furthermore, the role of the SARISEJAYA community in strengthening History learning is very important. Teachers at the education level will be able to adapt to the times through collaboration with the SARISEJAYA Community. On the other hand, Community members will gain knowledge related to the needs of History learning in the era of globalization as it is today. the conclusion is that creating interesting learning certainly requires a huge struggle. The learning needs of students must be optimized. The combination of cooperation between the education sector and the SARISEJAYA Community in Lubuklinggau City is very good in developing good, innovative, and relevant history learning with the needs of today's students.